2020
DOI: 10.1083/jcb.201903135
|View full text |Cite
|
Sign up to set email alerts
|

Syncrip/hnRNP Q is required for activity-induced Msp300/Nesprin-1 expression and new synapse formation

Abstract: Memory and learning involve activity-driven expression of proteins and cytoskeletal reorganization at new synapses, requiring posttranscriptional regulation of localized mRNA a long distance from corresponding nuclei. A key factor expressed early in synapse formation is Msp300/Nesprin-1, which organizes actin filaments around the new synapse. How Msp300 expression is regulated during synaptic plasticity is poorly understood. Here, we show that activity-dependent accumulation of Msp300 in the postsynaptic compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 86 publications
2
20
0
Order By: Relevance
“…The present finding is the first indication that Syp has a unique function in adult flies ( Fig 3 ) independent of its developmental effects ( Fig 4 ). At the subcellular and molecular level, previous studies have shown that Syp, in muscle cells at the Drosophila larval neuromuscular junction, can modulate the presynaptic vesicle release through regulating postsynaptic translation of a retrograde signal [ 30 ] and can regulate activity-dependent synaptic plasticity [ 58 ]. Similar functions have also been observed in mammalian SYNCRIP such that it is a component of neuronal RNA transport granules that can regulate dendritic morphology [ 48 , 59 61 ], and that it inhibits translation by competing with the poly(A) binding protein [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present finding is the first indication that Syp has a unique function in adult flies ( Fig 3 ) independent of its developmental effects ( Fig 4 ). At the subcellular and molecular level, previous studies have shown that Syp, in muscle cells at the Drosophila larval neuromuscular junction, can modulate the presynaptic vesicle release through regulating postsynaptic translation of a retrograde signal [ 30 ] and can regulate activity-dependent synaptic plasticity [ 58 ]. Similar functions have also been observed in mammalian SYNCRIP such that it is a component of neuronal RNA transport granules that can regulate dendritic morphology [ 48 , 59 61 ], and that it inhibits translation by competing with the poly(A) binding protein [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the subcellular and molecular level, previous studies have shown that Syp, in muscle cells at the Drosophila larval neuromuscular junction, can modulate the presynaptic vesicle release through regulating postsynaptic translation of a retrograde signal [30] and can regulate activity-dependent synaptic plasticity [58]. Similar functions have also been observed in mammalian SYNCRIP such that it is a component of neuronal RNA transport granules that can regulate dendritic morphology [48,[59][60][61], and that it inhibits translation by competing with the poly(A) binding protein [62].…”
Section: Discussionmentioning
confidence: 99%
“…Different hnRNP Q isoforms have been associated with differential splicing activity of the SMN2 exon 7 in the neurodegenerative disease SMA [ 144 ]. Further functions of hnRNP Q include the post-transcriptional modulation of circadian clock gene mRNAs levels [ 94 , 95 ], morphological development of neuromuscular junctions [ 194 ] and the exosomal sorting of specific micro RNAs [ 72 ]. Both hnRNP R and Q have been identified as potentially important regulators of neuronal homeostasis and cellular pathways associated with neurodegeneration [ 23 ].…”
Section: The Hnrnp Familymentioning
confidence: 99%